2014
DOI: 10.1159/000369140
|View full text |Cite
|
Sign up to set email alerts
|

Loss of AT-Rich Interactive Domain 1A Expression in Gastrointestinal Malignancies

Abstract: Objective: AT-rich interactive domain 1A (ARID1A) has recently been identified as a novel tumor suppressor in various tumor types. This study was designed to explore the clinical relevance and prognostic impact of ARID1A expression loss in colorectal cancer (CRC) and gastric cancer (GC). Methods: Immunohistochemistry for ARID1A was performed using tissue microarray blocks containing 196 CRCs and 275 GCs, along with paired normal mucosa. Data on clinicopathologic variables and oncologic outcomes of patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 35 publications
7
28
0
Order By: Relevance
“…In line with our results, Wei et al observed that 25.8% of colorectal cancer tumors had loss of ARID1A expression and 51.2% of the tumors had low ARID1A expression compared with adjacent nonmalignant tissue samples [21]. Overall, current IHC results and some previous studies [21,23,39,40] suggest that ARID1A loss is not rare in colorectal cancer tumors. However, the molecular basis of this downregulation remains to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our results, Wei et al observed that 25.8% of colorectal cancer tumors had loss of ARID1A expression and 51.2% of the tumors had low ARID1A expression compared with adjacent nonmalignant tissue samples [21]. Overall, current IHC results and some previous studies [21,23,39,40] suggest that ARID1A loss is not rare in colorectal cancer tumors. However, the molecular basis of this downregulation remains to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…In the CRC cell lines, ARID1A copy numbers were comparable with the control a tumor suppressor, and plays a key role in the progression of many types of cancer [13]. However, there are few studies that investigated the incidence and clinicopathologic importance of ARID1A loss in colorectal cancer and available published results are not conclusive [21,23,39]. For instance, Wei et al showed that loss of ARID1A expression was associated with distant metastasis and late TNM stage of CRC; however, they did not find any association between loss of ARID1A expression and age, gender, tumor location and tumor size [21].…”
Section: Discussionmentioning
confidence: 98%
“…As outlined in Table 2, the combined data from the literature [1518] as well as those observed in this study indicate a tendency toward a higher frequency of ARID1A loss in higher-stage tumors when compared with stage I tumors (7%–13.2% in stages II–IV versus 5.8% in stage I; P < .03). This is interesting because it suggests that tumors acquire ARID1A mutation as they progress.…”
Section: Discussionsupporting
confidence: 78%
“…Studies on CRC thus far have all been limited by the retrospective nature and small sample size that do not allow adequate control for all these competing factors. Consequently, none of the studies that analyzed either CRCs of all stages [1518] or CRCs stratified by MMR deficiency [18] have demonstrated a statistical significance in the survival status between ARID1A-loss and ARID1A-retained CRCs. The recent meta-analysis of 25 studies with 5651 patients reported loss of ARID1A associating with a shortened time to cancer-specific mortality [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation